Eccentricity-Based Topological Descriptors of First Type of Hex-Derived Network. (9th May 2022) - Babar, Usman; Naseem, Asim; Shaker, Hani; Zobair, Mian Muhammad; Ali, Haidar
Abstract : Graph theory has made significant progress in mathematical chemistry and has gained a lot of traction among scientists due to its numerous applications in mathematical chemistry. The numerical invariants of a molecular structure are known as molecular topological descriptors, and they are highly effective for predicting their bioactivity. A number of such indices are examined and applied in pharmaceutical research, chemistry, medication development, and other fields. The eccentricity-based Zagreb indices, total eccentricity, geometric arithmetic G A 4, atom-bond connectivity A B C 5, and average eccentricity indices of a hex-derived network of first type are computed in this article. We also provide analytically closed formulas for these descriptors, which may be used to investigate the underlying topologies.